A Case Report on Endodontic Management of a Rare Vertucci Type III Maxillary Canine - Hrudi Sundar Sahoo; R. Kurinji Amalavathy; D. Pavani (Case Reports in Dentistry)
Success in root canal treatment demands a thorough knowledge of usual root canal anatomy and its variations pertaining to every tooth. Variations in root canal anatomy are often accompanied by complex orientation of pulp tissues making a thorough mechanical and chemical debridement a challenge. Inability to treat such complexities often leads to endodontic failure. Upon a quick review of the literature, it has been noted that very few root canal complexities in maxillary canines have been reported. To be a successful clinician, one must be aware of such rare anatomical instances in maxillary canines. Based on possible branching of the root canal system, root canal configurations of permanent teeth were divided into eight different types by Vertucci. The classification included single to three separate root canals. This case report presents a permanent right maxillary canine which is single rooted having a single canal orifice and a root canal dividing into two canals (buccal and palatal) at the middle third of the root and then joining at the apical third, before exiting with a single apical foramen (Vertucci type III).